PHONOLOGICAL WORKING MEMORY IN CHILDREN WITH DEVELOPMENTAL LANGUAGE DISORDER AND TYPICALLY DEVELOPING CHILDREN - Neda Milošević Dedakin; Jovana Janjić (Istraživanja u Pedagogiji, 2025)
Introduction: One of the fundamental abilities underlying language development is phonological working memory. In this regard, the hypothesis is that children with specific language impairments have difficulties with phonological working memory, which may limit their language development. Objective: The aim of this study is to examine phonological working memory in children with typical language development and children with specific language impairments and to determine if there are differences in phonological working memory between these two groups of children. Method: The study included 120 children aged five years and eleven months to seven years, divided into two groups. The clinical group consisted of 40 children with a diagnosed specific language impairment, while the control group consisted of 80 children with typical language development. Instrument: To assess phonological working memory, we used tasks from the PreChip test, specifically tasks involving repetition of pseudowords and repetition of sentences. Results: It was found that children with specific language impairments performed worse than typically developing children on both pseudoword repetition and sentence repetition tasks. The performance on the pseudoword repetition task was statistically significantly different between the two groups (p = 0.000; r = 0.741), as was the performance on the sentence repetition task (p = 0.000; r = 0.827). Conclusion: Based on the results, it can be concluded that children with specific language impairments have difficulties with pseudoword and sentence repetition, implying that these children have difficulties with phonological working memory.